STUDENTS’ PERCEPTION TOWARDS THE USE OF MULTIMEDIA BASED TEACHING MATERIAL - Leora Grahadila Andovita; Asih Wahyuni (UNIVERSITAS PAKUAN, 2020)
The development of media in a conception of learning technology must have the following characteristics: (a) target oriented; (b) applying the concept of a systems approach; and (c) make use of varied learning resources. Thus the application of media and educational technology, can realize a concept of